Carbon material, preparation method and application thereof, and sodium ion battery

By reacting raw coal in alkali and acid liquid and subjecting high-temperature oxidation and carbonization treatment, amorphous carbon materials were prepared, which solved the problem of difficult to take into account both the instability and electrochemical performance of hard carbon materials, and achieved high capacity and high capacity of sodium ion batteries. High first-term efficiency and suitable for industrial applications.

CN119263252APending Publication Date: 2025-01-07CHINA ENERGY INVESTMENT CORP LTD +1

Patent Information

Application Number
CN202310830396.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing hard carbon materials are instability and cannot take into account both electrochemical performance and cost as the negative electrode material of sodium ion batteries. The treatment method using hydrofluoric acid is corrosive and safe, making it difficult to achieve industrial application.

Method used

By placing the raw coal in alkali and acid liquid, and undergoing high-temperature oxidation and carbonization treatment, amorphous carbon material is prepared, which is used as the negative electrode material for sodium ion batteries, improving its capacity and first-term effect, and is suitable for industrial applications.

Benefits of technology

The high capacity and high first-term efficiency of sodium ion batteries are achieved, and the preparation method is safe and suitable for industrial production. The Lc×La/(d002* oxygen-carbon ratio of the material is <210, 0.1C capacity>300mAh/g, and the first-term efficiency>85% .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004326808610000081
    Figure BDA0004326808610000081
Patent Text Reader

Abstract

The invention discloses a carbon material, a preparation method and application thereof, and a sodium ion battery, the preparation method comprises the following steps: 1) placing raw coal in alkali liquor and acid liquor for reaction to obtain pretreated coal; 2) performing high-temperature oxidation on the pretreated coal in an oxygen-containing atmosphere to obtain pre-oxidized coal; and 3) performing high-temperature carbonization treatment on the pre-oxidized coal to obtain the amorphous carbon material. When the prepared carbon material is used as a sodium-ion battery negative electrode material, the capacity and the first effect of a battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a carbon material, a preparation method and application thereof, and a sodium ion battery. Background Art

[0002] The lithium-ion battery industry market will usher in a blowout period, but lithium resources are scarce and unevenly distributed. Sodium has similar properties to lithium, abundant reserves, low cost and potential high safety. Therefore, sodium-ion batteries have great development prospects in large-scale energy storage applications. They have good cycle life, and are comparable to various types of lithium-ion batteries in terms of rate performance and high and low temperature performance. At the same time, they have resource advantages and have good application prospects in energy storage and other fields.

[0003] Hard carbon materials have a macroscopic non-graphite structure with large interlayer spacing and disordered microstructure, which is not easy to graphitize. Hard carbon precursors are abundant in sources, including resins (epoxy resins, phenolic resins, etc.), high molecular polymers, biomass, etc. Hard carbon has a high low-voltage platform capacity as an electrode material for sodium ion batteries and is one of the most promising negative electrode materials for sodium ion batteries. However, in the prior art, the source of hard carbon materials as negative electrode materials is unstable and cannot take into account both electrochemical performance (such as capacity, first effect) and cost.

[0004] CN 113381013 A discloses a coal-based hard carbon negative electrode material for sodium ion batteries, and its preparation method and application. The negative electrode material has a high capacity, but the initial efficiency is very low (about 80%). In addition, the study uses hydrofluoric acid for pore formation and purification. Hydrofluoric acid (HF) has the characteristics of strong corrosiveness and pungent odor, which causes serious damage to operators and reaction equipment. Therefore, the use of HF deashing in this study is not easy to achieve industrial application, and the initial efficiency of the material needs to be further improved. Summary of the invention

[0005] In view of this, the main purpose of the present invention is to provide a carbon material and its preparation method and application, and a sodium ion battery. When the carbon material is used as a negative electrode material for a sodium ion battery, the capacity and initial efficiency of the battery can be improved, and the preparation method is suitable for industrial application.

[0006] To achieve the above-mentioned object of the invention, the first aspect of the present invention provides a method for preparing a carbon material, comprising the following steps:

[0007] 1) placing raw coal in alkaline solution and acid solution to react and obtain pretreated coal;

[0008] 2) subjecting the pretreated coal to high temperature oxidation in an oxygen-containing atmosphere to obtain preoxidized coal; and,

[0009] 3) subjecting the pre-oxidized coal to high-temperature carbonization treatment to obtain the amorphous carbon material.

[0010] Furthermore, the raw coal has a volatile matter greater than 10%, and an oxygen-carbon ratio greater than 15%. Preferably, the volatile matter is 10%-50%, and the oxygen-carbon ratio is 15%-40%.

[0011] Furthermore, placing the raw coal in alkaline solution and acid solution for reaction comprises: soaking the raw coal in alkaline solution with a concentration of 10%-40% and acid solution with a concentration of 5%-10%.

[0012] Furthermore, the soaking temperature in the alkaline solution is 150-250° C., and the soaking time is 1-8 hours; the soaking temperature in the acid solution is room temperature, and the soaking time is 1-8 hours.

[0013] Furthermore, the D50 of the pretreated coal particles is 1-5000 μm, preferably 5-500 μm, and more preferably 5-20 μm.

[0014] Furthermore, the conditions of high temperature oxidation in step 2) include: treating at 50°C-500°C for 1-8 hours, with a heating rate of 5-10°C / min, and preferably a temperature of 150-300°C.

[0015] Furthermore, the conditions for the high temperature carbonization treatment in step 3) include: high temperature treatment at 1000°C-1600°C for 1-8 hours in an inert gas atmosphere, with a heating rate of 5-10°C / min; the inert gas is preferably nitrogen.

[0016] The second aspect of the present invention provides an amorphous carbon material obtained by the above preparation method, wherein Lc×La / (d002*oxygen-carbon ratio) of the amorphous carbon material is less than 210.

[0017] The third aspect of the present invention provides the use of the amorphous carbon material prepared by the above preparation method as a negative electrode material in a sodium ion battery.

[0018] A fourth aspect of the present invention provides a sodium ion battery comprising a negative electrode material made from the above-mentioned amorphous carbon material.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] The present invention first places raw coal in alkaline solution and acid solution for reaction, the purpose is to remove impurities and volatiles in the raw coal, and obtain pre-treated coal; then the pre-treated coal is subjected to high-temperature oxidation in an oxygen-containing atmosphere, the purpose is to introduce oxygen into the pre-treated coal, inhibit the graphitization process, and is conducive to the improvement of the capacity of the negative electrode material, and obtain pre-oxidized coal; then the pre-oxidized coal is subjected to high-temperature carbonization treatment to obtain an amorphous carbon material. The amorphous carbon material prepared by the present invention has a Lc×La / (d002*oxygen-carbon ratio) of less than 210. When it is used as a negative electrode material for a sodium ion battery, the capacity is relatively high, so that the 0.1C capacity of the sodium ion battery is greater than 300mAh / g, and the first efficiency is greater than 85%.

[0021] Other features and advantages of the present invention will be described in detail through the following detailed description. DETAILED DESCRIPTION

[0022] The present application is further described below in conjunction with embodiments, but the present application is not limited to the listed embodiments, but also includes equivalent improvements and modifications of the technical solutions defined in the claims attached to the present application.

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained from commercial channels.

[0025] The performance data of the embodiment of the present invention is obtained as follows:

[0026] X-ray powder diffractometer (XRD, D / max 2400, Cu Kα) was used to characterize the crystal structure of the material. The oxygen-carbon ratio was characterized by an elemental analyzer (Vario EL) based on the elemental composition of the sample.

[0027] D50 is obtained by testing with the MalvernMastersizer 2000 laser particle size analyzer of Malvern Instruments Ltd., UK;

[0028] The battery capacity and first efficiency (first coulomb efficiency) were charged and discharged by using the battery test system CT2001A battery tester of Wuhan Blue Electric Electronics Co., Ltd., with a current of 0.1C (1C=350mAh / g) and a voltage of 0-3V.

[0029] The first aspect of the present invention provides a method for preparing a carbon material, comprising the following steps:

[0030] 1) placing raw coal in alkaline solution and acid solution to react and obtain pretreated coal;

[0031] 2) subjecting the pretreated coal to high temperature oxidation in an oxygen-containing atmosphere to obtain preoxidized coal; and,

[0032] 3) subjecting the pre-oxidized coal to high temperature carbonization treatment to obtain an amorphous carbon material.

[0033] Preferably, the volatile matter of the raw coal is greater than 10%, and the oxygen-carbon ratio is greater than 15%. Preferably, the volatile matter is 10%-50%, and the oxygen-carbon ratio is 15%-40%. More preferably, the volatile matter is 30%-40%, and the oxygen-carbon ratio is 19%-30%. Coal with a relatively small volatile matter and oxygen-carbon ratio has low reactivity with oxygen during the oxidation process, and the introduced oxygen is limited, which cannot play a role in increasing the capacity. Coal with a relatively large volatile matter and oxygen-carbon ratio has too high reactivity with oxygen during the oxidation process, and the excessive oxygen introduced will affect the first coulomb efficiency. In summary, the present invention selects coal types with the above-mentioned volatile matter and oxygen-carbon ratio ranges to effectively improve the capacity and the first efficiency. The coal sample is isolated from the air and heated under specified conditions, and the organic matter in the coal is decomposed by heat to produce a part of liquid (at this time in a vapor state) and gaseous products with a smaller molecular weight. These products are called volatiles. The fraction of volatiles to the mass of the coal sample is called the volatile matter yield or simply volatiles; the oxygen and carbon in the above-mentioned oxygen-carbon ratio are measured by elemental analysis and are the elemental content.

[0034] Preferably, the cleaning of the raw coal in alkaline solution and acid solution includes: soaking the raw coal in alkaline solution with a concentration of 10%-40% and acid solution with a concentration of 5%-10% in sequence. In a specific example, the alkaline solution is selected from one or more aqueous solutions of sodium hydroxide or potassium hydroxide, and the acid solution is selected from one or more hydrochloric acid, sulfuric acid and phosphoric acid solutions. The present invention removes impurities and volatiles in the raw coal by using alkaline solution and acid solution. The removal of impurities is beneficial to the subsequent improvement of capacity when used as a negative electrode material, and the removal of volatiles is beneficial to the improvement of the initial coulomb efficiency. At the same time, the present invention can use mild alkaline solution and acid solution without destroying the structure of the coal itself, which also ensures the electrochemical properties of the negative electrode material. There is no limitation on the order of soaking in alkaline solution and acid solution in the present invention.

[0035] In some embodiments, the raw coal is first soaked in an alkali solution with a concentration of 10%-40% and then taken out and dried, and then the dried raw coal is soaked in an acid solution with a concentration of 5%-10%, washed with water until neutral, and then taken out and dried. There is no special limitation on the drying parameters, and reference can be made to the raw coal drying process in the art, such as drying at 80°C for 5 hours.

[0036] Preferably, the soaking temperature in the alkaline solution is 150°C-250°C, and the soaking time is 1-8h; the soaking temperature in the acid solution is room temperature, such as 20-40°C, and the soaking time is 1-8h.

[0037] Preferably, the D50 of the pretreated coal particles is 1-5000 μm, preferably 5-500 μm, more preferably 5-20 μm, and the above range is suitable for the subsequent preparation of negative electrode materials.

[0038] Preferably, the conditions of high temperature oxidation in step 2) include: treating at 50°C-500°C for 1-8 hours, heating rate of 5-10°C / min, and preferably temperature of 150-300°C. A suitable oxidation rate is suitable for industrial scale-up on the one hand, and affects the oxygen content introduced on the other hand. Oxidation within the above conditions is suitable for industrial scale-up and is conducive to controlling the oxygen content. In some embodiments, the oxygen-containing gas is pure oxygen or air.

[0039] Preferably, the conditions for the high temperature carbonization treatment in step 3) include: high temperature treatment at 1000°C-1600°C for 1-8 hours in an inert gas atmosphere with a heating rate of 5-10°C / min; the inert gas is preferably nitrogen.

[0040] The second aspect of the present invention provides an amorphous carbon material prepared by the above preparation method, wherein Lc×La / (d002*oxygen-carbon ratio) of the amorphous carbon material is less than 210. Wherein, d002 represents the 002 crystal plane spacing of the carbon material. Preferably, 180<Lc×La / (d002*oxygen-carbon ratio)<210.

[0041] The third aspect of the present invention provides the use of the amorphous carbon material prepared by the above preparation method as a negative electrode material in a sodium ion battery.

[0042] A fourth aspect of the present invention provides a sodium ion battery comprising a negative electrode material made from the above-mentioned amorphous carbon material.

[0043] The present invention is described in detail below by way of examples:

[0044] Example 1

[0045] The method for preparing the carbon material according to the embodiment of the present invention comprises the following steps:

[0046] 1) Acid-base reaction: select coal with volatile matter of 32.6% and oxygen-carbon ratio of 28.9% as raw coal, with particle size D50=10 μm, place the raw coal in a 10% sodium hydroxide aqueous solution at 170° C. for reaction for 5 h, take out the raw coal and dry it at 80° C. for 5 h in a vacuum environment, then place it in a 5% HCl solution at 20° C. for reaction for 5 h, wash it with water until it is neutral, take out the raw coal and dry it at 80° C. for 5 h in a vacuum environment to obtain pretreated coal;

[0047] 2) Pre-oxidation: The pre-treated coal is treated at 200°C for 5 hours in an air atmosphere at a heating rate of 10°C / min to obtain pre-oxidized coal;

[0048] 3) Carbonization: The pre-oxidized coal was treated at 1200°C for 3 hours in a nitrogen atmosphere at a heating rate of 10°C / min, and then naturally cooled to obtain an amorphous carbon material.

[0049] Example 2

[0050] 1) Acid-base reaction: select coal with volatile matter of 33.2% and oxygen-carbon ratio of 19.1% as raw coal, with particle size D50=8 μm, place the raw coal in a 10% sodium hydroxide aqueous solution at 180°C for reaction for 5 hours, take out the raw coal and dry it at 80°C in a vacuum environment for 5 hours, then place it in a 5% HCl solution at 20°C for reaction for 8 hours, wash it with water until it is neutral, take out the raw coal and dry it at 80°C in a vacuum environment for 5 hours to obtain pretreated coal;

[0051] 2) Pre-oxidation: The pre-treated coal is treated at 300°C for 5 hours in an air atmosphere with a heating rate of 10°C / min to obtain pre-oxidized coal;

[0052] 3) Carbonization: The pre-oxidized coal was treated at 1400°C for 3 hours in a nitrogen atmosphere at a heating rate of 10°C / min, and then cooled naturally to obtain an amorphous carbon material.

[0053] Example 3

[0054] Acid-base reaction: select coal with volatile matter of 35.1% and oxygen-carbon ratio of 20.1% as raw coal, with particle size D50=10 μm, place the raw coal in a 10% sodium hydroxide aqueous solution at 200°C for reaction for 5 hours, take out the raw coal and dry it at 80°C in a vacuum environment for 5 hours, then place it in a 5% HCl solution at room temperature of 30°C for reaction for 5 hours, wash it with water until it is neutral, take out the raw coal and dry it at 80°C in a vacuum environment for 5 hours to obtain pretreated coal;

[0055] 2) Pre-oxidation: The pre-treated coal is treated at 200°C for 5 hours in an air atmosphere at a heating rate of 10°C / min to obtain pre-oxidized coal;

[0056] 3) Carbonization: The pre-oxidized coal was treated at 1300°C for 3 hours in a nitrogen atmosphere at a heating rate of 10°C / min, and then cooled naturally to obtain an amorphous carbon material.

[0057] Embodiment 4-5

[0058] In Examples 4-5, raw coal with different volatile matter and carbon-oxygen ratio from those in Example 1 is selected, and the remaining processes and parameters are the same as those in Example 1.

[0059] Example 6

[0060] The difference from Example 1 is that the raw coal is placed in a 10% sodium hydroxide aqueous solution and reacted at 100° C. for 5 hours.

[0061] Example 7

[0062] The difference from Example 1 is that the pretreated coal is treated at 100° C. for 5 h in an air atmosphere.

[0063] Example 8

[0064] The difference from Example 1 is that the volatile matter of the raw coal is 55%, and the oxygen-carbon ratio is 40%.

[0065] Comparative Example 1

[0066] In Comparative Example 1, raw coal with different volatile matter and carbon-oxygen ratio from those in Example 1 was selected, and the remaining processes and parameters were the same as those in Example 1.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that step 2) pre-oxidation is not performed.

[0069] Comparative Example 3

[0070] The difference from Example 1 is that step 1) acid-base reaction is not performed.

[0071] Comparative Example 4

[0072] The difference from Example 1 is that step 1) uses hydrofluoric acid and hydrochloric acid to react, specifically comprising: placing the raw coal in 4 mol·L -1 Stir continuously in hydrochloric acid for 6 hours, take out the raw coal and place it in a vacuum oven at 80℃ to dry for 24 hours. Then add the dried raw coal into 10wt% hydrofluoric acid and stir continuously for 6 hours, wash with water until neutral, take out the raw coal and place it in a forced air oven at 50℃ to dry for 24 hours.

[0073] Comparative Example 5

[0074] The difference from Example 1 is that pre-oxidation is performed first and then acid-base cleaning is performed. The specific steps include:

[0075] 1) Pre-oxidation: The pre-treated coal is treated at 200°C for 5 hours in an air atmosphere with a heating rate of 10°C / min to obtain pre-oxidized coal;

[0076] 2) Acid-base reaction: select coal with volatile matter of 32.6% and oxygen-carbon ratio of 28.9% as raw coal, with particle size D50=10 μm, place the raw coal in a 10% sodium hydroxide aqueous solution at 170°C for reaction for 5 hours, take out the raw coal and dry it at 80°C in a vacuum environment for 5 hours, then place it in a 5% HCl solution at room temperature of 20°C for reaction for 5 hours, wash it with water until it is neutral, take out the raw coal and dry it at 80°C in a vacuum environment for 5 hours to obtain pretreated coal;

[0077] 3) Carbonization: The pre-oxidized coal was treated at 1200°C for 3 hours in a nitrogen atmosphere at a heating rate of 10°C / min, and then naturally cooled to obtain an amorphous carbon material.

[0078] The amorphous carbon material prepared in Examples 1-8 and Comparative Examples 1-5 is used as the negative electrode, and the sodium ion battery is prepared according to a conventional method. Conventional method, for example, the preparation process of a button battery is as follows: the amorphous carbon material is used as the negative electrode material, and the conductive carbon black Super P and the binder polyvinylidene fluoride (PVDF) are mixed uniformly in a mass ratio of 92:3:5, and the solvent N-methylpyrrolidone (NMP) is added, and stirred into a uniform negative electrode slurry. The negative electrode slurry is evenly applied to the aluminum foil with a scraper, and dried to obtain a negative electrode sheet. The obtained negative electrode sheet is punched into a sheet with a diameter of 12 mm and transferred to an MBraun2000 glove box (Ar atmosphere, H2O and O2 concentrations less than 0.1×10 -6 Volume %), with metallic sodium sheet as reference electrode, assembled into button cell.

[0079] The properties of the amorphous carbon materials and batteries obtained in the above Examples 1-8 and Comparative Examples 1-5 are shown in Table 1 below.

[0080] Table 1

[0081]

[0082] It can be seen from the data in Table 1 that the performance of the charging capacity and the first coulomb efficiency of Examples 1-5 of the present invention is better. In Examples 6-7, due to the inappropriate temperature of the alkali treatment or the pre-oxidation temperature, the capacity and the first efficiency are reduced, and the effect is reduced. The reason is that the low alkali treatment temperature still makes the impurity content in the coal high, and the lower pre-oxidation temperature causes the oxygen content to decrease, which affects the embedding and adsorption of sodium ions in the negative electrode material. In Example 8, due to the inappropriate selection of raw coal, the first efficiency is reduced and the effect is reduced. The reason is that the volatile matter and oxygen-carbon ratio are relatively high, resulting in an increase in the consumption of irreversible sodium ions during the first charge and discharge process.

[0083] Comparative Example 1 uses a type of coal with too low volatile matter and oxygen-carbon ratio, and the charging capacity and the first coulomb efficiency are significantly reduced. Comparative Example 2 does not set a pre-oxidation step, and Comparative Example 3 does not set an acid-base reaction step. Comparative Example 4 uses hydrofluoric acid reaction and the order of acid-base reaction and pre-oxidation is changed in Comparative Example 5. Compared with Example 1, the charging capacity and the first coulomb efficiency of the amorphous carbon materials prepared in Comparative Examples 2-5 are reduced. Among them, the use of hydrofluoric acid in Comparative Example 4 may destroy the structure of the coal itself on the one hand, and on the other hand, after the coal is treated with hydrofluoric acid, the specific surface area of ​​the material is significantly increased. In the negative electrode material, the larger specific surface area will reduce the first coulomb efficiency, thereby affecting the reversible capacity. In Comparative Example 5, pre-oxidation is performed first and then acid-base reaction. The acid-base reaction will reduce the content of oxygen introduced in the pre-oxidation process, which will reduce the capacity and first efficiency, and the electrochemical performance will decrease.

[0084] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are within the spirit scope of the present invention.

Claims

1. A method for preparing a carbon material, characterized in that: The steps include: 1) placing raw coal in alkaline solution and acid solution to react and obtain pretreated coal; 2) subjecting the pretreated coal to high temperature oxidation in an oxygen-containing atmosphere to obtain preoxidized coal; and, 3) subjecting the pre-oxidized coal to high temperature carbonization treatment to obtain an amorphous carbon material.

2. The method for preparing the carbon material according to claim 1, characterized in that: The volatile matter of the raw coal is greater than 10%, and the oxygen-carbon ratio is greater than 15%; preferably, the volatile matter of the raw coal is 10%-50%, and the oxygen-carbon ratio is 15%-40%.

3. The method for preparing the carbon material according to claim 1, characterized in that: Placing the raw coal in alkaline solution and acid solution for reaction comprises: soaking the raw coal in alkaline solution with a concentration of 10%-40% and acid solution with a concentration of 5%-10%; preferably, the alkaline solution is selected from one or more aqueous solutions of sodium hydroxide or potassium hydroxide, and the acid solution is selected from one or more solutions of hydrochloric acid, sulfuric acid and phosphoric acid.

4. The method for preparing the carbon material according to claim 3, characterized in that: The soaking temperature in the alkaline solution is 150°C-250°C, and the soaking time is 1-8h; the soaking temperature in the acid solution is room temperature, and the soaking time is 1-8h.

5. The method for preparing the amorphous carbon material according to claim 1, characterized in that: The D50 of the pretreated coal particles is 1-5000 μm, preferably 5-500 μm, and more preferably 5-20 μm.

6. The method for preparing the amorphous carbon material according to claim 1, characterized in that: The conditions of high temperature oxidation in step 2) include: treating at 50°C-500°C for 1-8 hours, heating rate of 5-10°C / min, preferably at 150-300°C.

7. The method for preparing the amorphous carbon material according to claim 1, characterized in that: The conditions for the high temperature carbonization treatment in step 3) include: high temperature treatment at 1000° C.-1600° C. for 1-8 hours in an inert gas atmosphere, with a heating rate of 5-10° C. / min.

8. The carbon material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The amorphous carbon material has a Lc×La / (d002*oxygen-carbon ratio) of less than 210.

9. Use of the carbon material prepared by the preparation method according to any one of claims 1 to 7 as a negative electrode material in a sodium ion battery.

10. A sodium ion battery comprising a negative electrode material made from the carbon material according to claim 8 or the carbon material prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Coal-based hard carbon negative electrode material of sodium ion battery, preparation method and application thereof

    CN113381013A

  • Amorphous carbon material and preparation method thereof, sodium ion battery negative electrode and sodium ion battery

    CN113493193A

  • Carbon material for sodium-ion battery negative electrode, preparation method of carbon material, sodium-ion battery negative electrode plate and sodium-ion battery

    CN114956037A

  • Preparation method of high-rate long-cycle pyrolytic carbon negative electrode material for sodium storage

    CN116119643A

  • Preparation method of sodium ion battery negative electrode carbon material

    CN116119646A

Cited By

  • Method for preparing coal-based hard carbon material by oxygen-assisted low-temperature etching of amorphous components in coal precursor

    CN119976792A